2018
DOI: 10.1007/s00439-018-1932-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of isolated pediatric cataracts: extreme heterogeneity and variable inheritance patterns within genes

Abstract: Pediatric cataract represents an important cause of pediatric visual impairment. While both genetic and environmental causes for pediatric cataract are known, a large proportion remains idiopathic. The purpose of this review is to discuss genes involved in isolated pediatric cataract, with a focus on variable inheritance patterns within genes. Mutations in over 52 genes are known to cause isolated pediatric cataract, with a major contribution from genes encoding for crystallins, transcription factors, membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 121 publications
0
28
0
1
Order By: Relevance
“…In crystallin genes, non sense-mediated decay is determinant to whether the mutant alleles will have recessive or dominant effects. Thus, truncating mutations which appear in the initial coding sequences of the gene will be affected by non sense-mediated decay and follow a recessive pattern; whereas mutations in the final exon will be associated with dominant disease [ 16 ]. Mutations in crystallin genes accounted for the majority of hereditary congenital cataracts in our study (30%), which was an expected result as this is the most frequent mutation reported up to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In crystallin genes, non sense-mediated decay is determinant to whether the mutant alleles will have recessive or dominant effects. Thus, truncating mutations which appear in the initial coding sequences of the gene will be affected by non sense-mediated decay and follow a recessive pattern; whereas mutations in the final exon will be associated with dominant disease [ 16 ]. Mutations in crystallin genes accounted for the majority of hereditary congenital cataracts in our study (30%), which was an expected result as this is the most frequent mutation reported up to date.…”
Section: Discussionmentioning
confidence: 99%
“…Early intervention is crucial due to the high risk of amblyopia. Cataract surgery in babies and infants has a high risk of postoperative complications and it is a challenge to achieve a good visual acuity despite timely intervention and adequate follow-up [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The utility of trifocal and extended depth of focus intraocular lenses in particular requires accurate centration to provide optimal visual outcomes and minimize photic phenomena such as glare and halo. [1][2][3] Angle kappa has been used as a measure of centration in both refractive and lens-based surgery. It is defined as the angle difference between the visual axis (theoretical axis connecting the point of fixation with the nodal points and the fovea) and pupillary axis (line perpendicular to the cornea that passes through the center of the pupil).…”
Section: Supporting Informationmentioning
confidence: 99%
“…Congenital cataract are clinically and genetically heterogeneous, displaying various phenotypes [1]. So far nearly 50 genes have been found causing mostly isolated congenital cataracts broadly including genes encoding lens soluble proteins -crystallins; membrane proteins-gap junctions, aquaporins, receptor tyrosine kinase gene EPH receptor A2, an endoplasmic reticulum membrane-embedded protein, Wolframin, chromatin modifying protein-4B, lens integral membrane protein; AQP0, Connexin 50 and LIM2 cytoskeletal proteins-filensin, phakinin, vimentin and genes encoding transcription or developmental factors EYA1, MAF, FOXE3, VSX2, PAX6, PITX3 and HSF4 (https :// cat-map.wustl.edu/) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%